Knowledge, Attitude and Smoking Patterns Among Pregnant Women: A Jordanian Perspective - Jehan Hamadneh; Shereen Hamadneh; Zouhair Amarin; Soha Al-Beitawi (Ubiquity Press, 2021)
Background: Smoking during pregnancy is one of the main modifiable factors associated with perinatal morbidity and mortality and maternal complications. Literature is scant regarding smoking habits of pregnant women in Jordan. Objectives: To investigate smoking patterns and attitudes of Jordanian pregnant women towards smoking. Methods: A cross-sectional survey of patterns and attitudes towards smoking among 436 mothers attending healthcare facilities in the Governorate of Irbid, Jordan, between August and September 2019. Results: Out of 436 pregnant women in the Governorate of Irbid, Jordan, 13 (2.9%) quit smoking once pregnancy was conformed, and 77 (17.6%) continued to smoke. Pregnant non-smokers believed that hookah and electronic cigarettes are as bad to health as cigarettes, while smokers believed that hookah and electronic cigarettes are less hazardous than cigarettes (5.19% versus 21.99%, p = 0.001, and 6.49% versus 19.37%, p = 0.009, respectively). Non-smokers were significantly more aware regarding the hazards of smoking on perinatal outcomes, such as abortion (31.94% versus 10.39%, p = 0.001), placental abruption (31.94% versus 10.39%, p = 0.001), intrauterine growth restriction and fetal malformations (36.65% versus 14.29%, p = 0.007), fetal death (30.89% versus 6.49, p < 0.001), neonatal pulmonary diseases (44.50% versus 24.68%, p = 0.024), neonatal asthma (47.12% versus 28.57%, p = 0.038), and ear diseases (42.41% versus 20.8%, p = 0.012). Conclusion: There is a high prevalence of smokers among pregnant women in Jordan. The level of awareness regarding long-term consequences of tobacco use remains low. Educational programs should include information about the hazards of all forms of smoking. Pregnancy provides a good opportunity for promoting smoking cessation.